Efeito de espaçamento e níveis de adubação na produção de frutos maduros de pimentão (Capscium annuum L) - Ferreira da Silva, Roberto; Couto, Flávio A.A.; Tigchelaar, Edward; Francisco da Silva, José; Maffia de Oliveira, Laede (Revista Ceres, 2025)
The object of this workwas to study the effects of ferti- lizer levels and spacing on the production of mature fruits of pepper, cultivar "Ikeda".